Analisis Pengaruh Efektivitas Dan Manfaat E-Commerce Terhadap Sikap Dan Perilaku Pengguna Dengan Menggunakan Metode TAM (Studi Kasus: UKM Kota Palembang) - Yulistia Yulistia (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2017)
The appropriateuse of technology make us more good at utilizing it. Especially with online shopping provided by the business in building and deploying their business through a computer network. We know that many people who are busy with their work that make them do not have a lot of time to be able to spend time doing conventional business when they need it. Utilization of information and communication technology for the benefit of society and business especially Small and Medium Enterprises (SME), has been applied in various forms. One form of information technology application is E-Commerce system as the the use of information and communication technology to promote sales online.Along with the advancement of technologies, E-Commerce can be developed to improve the effectiveness and quality in sales and purchases. The E-Commerce system has a number of facilities such as online shopping, testimony, how to send, and so much more. This research describes the results of research on the extent of users attitudes and behavior, in this case is SME in Palembang, utilize information technology in the form of E-Commerce by using Theory Acceptance Model (TAM) method, so it can be known how far the effectiveness and benefits of E-Commerce system is in helping media sales and purchases online